THE EFFICACY OF CHATGPT IN ENHANCING WRITING PROFICIENCY AMONG UNIVERSITY STUDENTS - Mawardi; Ibnu Hajar; Jumaida Fajar Nassriati; T. Muntazar; Helmiyadi (RADJA PUBLIKA, 2025)
This study examines the efficacy of ChatGPT as an AI-assisted learning tool to improve undergraduate English department students' academic writing skills at Bumi Persada University in Indonesia. Twelve participants participated in the study, which used a mixed-methods research methodology. Lexical complexity, grammatical precision, and textual coherence are three important aspects of writing proficiency that were quantitatively measured using a pre-test and post-test paradigm. A deeper understanding of the student experience was made possible by qualitative data collected via semi-structured interviews and comprehensive questionnaires. The results show that there were notable benefits to including ChatGPT in the writing process. Notably, students' writing quality significantly improved, they became more motivated and involved in writing assignments, and they became more capable of learning on their own. However, the study also discovered a significant challenge: an overreliance on AI-generated ideas, which may impede the development of autonomous critical thinking and unique composition skills. The study finds that, while ChatGPT is a beneficial additional tool for second language writing pedagogy, its adoption necessitates careful instructional design to reduce the hazards of dependency and maximize the advantages for long-term skill acquisition.